2022
DOI: 10.30897/ijegeo.1128985
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Yield Prediction with Machine Learning based on MODIS and Landsat NDVI Data at Field Scale

Abstract: Accurate estimation of wheat yield using Remote Sensing-based models is critical in determining the effects of agricultural drought and sustainable food planning. In this study, Winter wheat yield was estimated for large fields and producer fields by applying Normalized Difference Vegetation Index (NDVI) based linear models (simple linear regression and multiple linear regression) and Machine Learning (ML) techniques (support vector machine_svm, multilayer perceptron_mlp, random forest_rf). In this study, depe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…The approximate average increase in the grain yields of spring wheat was about 6.7 t ha-1, with an increase of 0.1 in NDVI value. Tuğaç et al (2022) found that the highest correlation between NDVI and yield was during the flowering period (R²= 0.63). They also found that the best prediction performance was achieved with the MLP model for MODIS, with a root mean square error (RMSE) ranging from 0.23-0.65 t ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The approximate average increase in the grain yields of spring wheat was about 6.7 t ha-1, with an increase of 0.1 in NDVI value. Tuğaç et al (2022) found that the highest correlation between NDVI and yield was during the flowering period (R²= 0.63). They also found that the best prediction performance was achieved with the MLP model for MODIS, with a root mean square error (RMSE) ranging from 0.23-0.65 t ha -1 .…”
Section: Discussionmentioning
confidence: 99%
“…The results of this study also demonstrated that in 2022, RVI and NDVI showed a significant positive correlation with seed yield, with the highest correlation coefficient observed at the heading stage. However, as the growth stages progressed, the correlation coefficients gradually declined, which may be related to changes in leaf chlorophyll content and water content [ 42 ]. In conclusion, using data at the heading stage for smooth bromegrass seed yield prediction achieved the highest performance.…”
Section: Discussionmentioning
confidence: 99%
“…Here, critical phenological states which may hold information necessary to estimate yield amount may be missed. Conversely, at farm-level, [13] deduced that using Landsat improved wheat prediction suggesting the appropriateness of higher spatial resolution for small spatial units.…”
Section: Benefiting From Improved Spatial Resolutionmentioning
confidence: 98%